Practices and Challenges of Guidance and Counseling Services in Secondary Schools - Aminu Jibril Arfasa; Fisseha Mikrie Weldmeskel (Ital Publication, 2020)
The purpose of this study was to examine the practices and challenges of guidance and counseling services in southwest Ethiopia secondary schools with the intention of understanding the state of secondary school guidance and counseling and forward improvement options to student service. The study employs a descriptive survey design that involves quantitative and qualitative research methods. The study participants were 392 students and 108 teachers who were selected from the secondary schools of southwest Ethiopia by systematic random sampling. Moreover, 8 counselors, 8 principals, and 8 educational bureau officers were selected by a means of availability sampling. The data for the study were collected by the administration of questionnaires and the use of oral interviews. The quantitative data were analyzed using the frequency of student visits to guidance and counseling office and mean perception score on practices of guidance and counseling. The qualitative data were analyzed using the thematic analysis method with a focus on the major challenges of guidance and counseling services in the sampled schools. The result of the study showed that the majority of secondary school students never visit guidance and counseling offices. The mean perception score of students and teachers towards the usefulness of the service was positive though the provision was either very much limited or most of the time unavailable. The services of guidance and counseling are also influenced by several challenges such as the lack of professionally trained counselors and the required facilities. The researchers conclude the implication of guidance and counseling service and the associated challenges to considerably influence secondary school student learning and personal wellbeing.